The p-ZnO:N/i-Al2O3/n-GaN heterostructure—electron beam induced profiling, electrical properties and UV detectivity. (13th July 2015) - Przezdziecka, E; Chusnutdinow, S; Guziewicz, E; Snigurenko, D; Stachowicz, M; Kopalko, K; Reszka, A; Kozanecki, A
Abstract: The new type of a p-i-n structure consists of a single acceptor doped ZnO:N film grown by plasma assisted molecular beam epitaxy, a thin isolating Al2 O3 layer grown by atomic layer deposition method and n -type GaN template. The maximum forward-to-reverse current ratio I F / I R in the obtained diode is about 8   ×   10 6 at  ±7 V. Electron-beam-induced current measurements confirmed the presence of a p - i - n junction and the presence of the isolating layer located at the p -ZnO/ n- GaN interface. The diffusion length of carriers was calculated. The heterostructure exhibits an absorption in the UV range and the ratio between light (UV) and dark current is above four orders of magnitude.